Preliminary evidence for progressive prefrontal abnormalities in adolescents and young adults with bipolar disorder - Kalmar, Jessica H. (2009)
Previous cross-sectional study of ventral prefrontal cortex (VPFC) implicated progressive volume abnormalities during adolescence in bipolar disorder (BD). In the present study, a within-subject, longitudinal design was implemented to examine brain volume changes during adolescence/young adulthood. We hypothesized that VPFC volume decreases over time would be greater in adolescents/young adults with BD than in healthy comparison adolescents/young adults (HC). Eighteen adolescents/young adults (10 with BD I and 8 HC participants) underwent two high resolution magnetic resonance imaging scans over approximately two-years. Regional volume changes over time were measured. Adolescents/young adults with BD displayed significantly greater volume loss over time, compared to HC participants, in a region encompassing ventral and rostral PFC and extending to rostral anterior cingulate cortex (p<0.05). Additional areas where volume change differed between groups were observed. While data should be interpreted cautiously due to modest sample size, this study provides preliminary evidence to support the presence of accelerated loss in ventral and rostral PFC volume in adolescents/young adults with BD.